Development of data, models and techniques to determine optimal reliability level of electric power supply for the Philippines. - Viray, Francisco L. (Philippine Engineering Journal)
This study develops models and techniques to determine optimal reliability level of electric power supply for the Philippines using data from NPC Luzon grid. A survey of outage cost incurred by industrial firms in Metro Manila and suburbs from January to June 1990 was used to develop the outage cost model. The cost of increasing reliability and the cost of having an unreliable one, from the point of view of the national economy are combined to determine the optimal level which is the point where the total cost is minimum.